Spatial dynamics of AIDS incidence in the elderly in Rio de Janeiro, Brazil, 1997-2011 - Nádia Cristina Pinheiro Rodrigues; Andrea Sobral de Almeida; José Ueleres Braga; Gisele O'Dwyer; Paulo Cavalcante Apratto Junior; Regina Paiva Daumas; Valéria Teresa Saraiva Lino; Mônica Kramer de Noronha Andrade; Denise Leite Maia Monteiro; Mônica Bastos de Lima Barros (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
The dynamics of the spread of the AIDS epidemic ranges according to the characteristics of each geographical region in different population groups. The aim of this study was to evaluate spatial and temporal trends of the AIDS epidemic among the elderly in the State of Rio de Janeiro, Brazil. A retrospective study using spatial analysis techniques was conducted among AIDS cases (≥ 60 years) diagnosed from 1997-2011. The Poisson regression model was used to assess the relationship between year of diagnosis and incidence of AIDS, adjusted by sex. The AIDS epidemic began in the south coast of the state and gradually reached neighboring cities. The highest rates were found in regions around Rio de Janeiro and Niterói cities. The highest smoothed rates of the period were observed in Niterói in 2002-2006: 11.87/100,000 (men) and 8,5/100,000 (women). AIDS incidence rates among the elderly have stabilized in recent decades. To prevent HIV from spreading further among the general population, greater attention should be given to the older population.